RISK FACTORS AND PREVENTION OF PRESSURE ULCER IN SPINE CORD INJURY PATIENTS. EXPERIENCE OF MEMBERS OF NURSING TEAM AT FMRP - USP HOSPITAL - Nogueira, Paula Cristina; Caliri, Maria Helena L.; Santos, Cláudia B. (Medicina (Ribeirao Preto), 2002)
Pressure ulcers are frequent in spinal cord patients and can bring complication as osteomyelitis, sepses, amputation and even death. It interferes on quality of life of patients and families and brings difficulties for rehabilitation access. Being that, prevention or treatment in their initial stages needs to be the goals of a quality care. This study had as objectives to identify the causes of pressure ulcer in spinal cord injury patients and to describe prevention measures considered important as seem by professional nurses, nurses technicians and nurses auxiliaries, members of nursing team on an university hospital in Brazil. Through a survey, data was collected using an validated instrument containing 35 phrases descriptors of risk factors and 18 descriptors of preventive interventions. Each of 85 participants gave a value from 1 to 7 to the importance of the item and mean, standard deviation analysis of variance was calculated. The results of descriptive analysis and inferential statistics showed that the nursing team identified as important factors related to patient, to institutional structure and process of care. By their perception patients with spinal cord injury present immobility and impaired sensory perception, being dependent for mobilization. The process and structure of care does not respond to this need so the turning of patient is not rigorously done and bed mattress are not adequate what causes an excess of pressure on bone prominence. After discharge, the problem continues as families do not have enough knowledge and do not care adequately. Related to preventive measures there were differences between professional nurses and nurses technicians/auxiliaries. The former considered every measure as important but nurses technicians and auxiliaries did not and discrepancies were found between what they see as causes for pressure ulcer and what they consider important as preventive measures to minimize the problem.